1955
DOI: 10.1084/jem.102.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Immunological Response to Foreign Tumor Transplants in the Mouse

Abstract: Transplantation immunity is the state of heightened resistance to a tissue graft which develops after an earlier graft has been broken down. Techniques for the detection of transplantation immunity have been developed by Medawar (1, 2) for skin, and by Mitchison (3, 4) for transplantable tumors. Ceils from the lymphoid tissue of immunized mice have been shown to possess the power of transferring immunity, by Brncic, Hoecker, and Gasic (5) and Mitchison (3, 4) with transplantable tumors, and by Biningham, Brent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
2

Year Published

1955
1955
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(87 citation statements)
references
References 15 publications
3
80
0
2
Order By: Relevance
“…Subcutaneous injection of cells bearing foreign histocompatibility antigens is a potent stimulus of cell-mediated immunity (13). Furthermore, following such sensitization there occurs a time-dependent difference in cell-mediated immune functions between spleen and nondraining lymph node cells and draining lymph node cells (14).…”
Section: Resultsmentioning
confidence: 99%
“…Subcutaneous injection of cells bearing foreign histocompatibility antigens is a potent stimulus of cell-mediated immunity (13). Furthermore, following such sensitization there occurs a time-dependent difference in cell-mediated immune functions between spleen and nondraining lymph node cells and draining lymph node cells (14).…”
Section: Resultsmentioning
confidence: 99%
“…The only differences found lay in the direction of prolonged survival of grafts in the serum-injected mice. Similarly, Mitchison (9)(10)(11) found that the transfer of serum from immunized donors did not bring about inhibition of tumor growth in the secondary hosts of his experiments; in fact, there was evidence that the test grafts grew more rapidly in those mice than in the control recipients.…”
Section: The Transfer Of the Pre-injection E~ect By Lymph Node Cellsmentioning
confidence: 93%
“…(Received for publication, March 24, 1955) In preceding papers (1)(2)(3) it has been shown that heightened resistance to certain tumor homografts in mice can be transferred to secondary hosts by lymph node cells, but not by serum. Similar results have been reported by Billingham,Brent,and Medawar (4), with resistance to homografts of skin.…”
mentioning
confidence: 99%